Renoprotective effects of atorvastatin compared with pravastatin on progression of early diabetic nephropathy. Issue 3 (27th November 2014) - Takazakura, Akiko; Sakurai, Masaru; Bando, Yukihiro; Misu, Hirofumi; Takeshita, Yumie; Kita, Yuki; Shimizu, Akiko; Hayakawa, Tetsuo; Kato, Ken‐ichiro; Kaneko, Shuichi; Takamura, Toshinari
Abstract: Introduction: Several studies have shown that statins suppress the progression of diabetic nephropathy. However, few reports have directly compared the renoprotective effects between potent and conventional statins. Materials and Methods: Patients with diabetic nephropathy, selected as those with a serum creatinine level of 0.9–1.5 mg/dL and simultaneously having either microalbuminuria or positive proteinuria, were randomly assigned to one of three groups: a conventional diet therapy group, a group given 10 mg of pravastatin and a group given 10 mg of atorvastatin. Renal function was evaluated before and after a 12‐month period of therapy. Results: The atorvastatin group had a significant decrease in low‐density lipoprotein cholesterol at 3 months and thereafter compared with the other groups. The urinary albumin‐to‐creatinine ratio significantly decreased in the atorvastatin group; the degree of this decrease was significantly greater than that in the diet therapy group. The kidney function estimated with cystatin C (CysC) and the estimated glomerular filtration rate calculated from CysC were significantly preserved in the atorvastatin group compared with the pravastatin group. In a multivariate regression analysis, the use of atorvastatin was the only explanatory variable for the changes in CysC; this was independent of changes in low‐density lipoprotein cholesterol. Conclusions: Atorvastatin is more effective than pravastatin for the prevention of increase in CysC, and this renoprotective effect was considered to a result of the pleiotropic effect of atorvastatin independent of its lipid‐lowering effect. This study was registered with UMIN (no. UMIN 000001774). Abstract : Atorvastatin is more effective than pravastatin for the prevention of increase in Cystatin C, and this renoprotective effect was considered to be due to the pleiotropic effect of atorvastatin independent of its lipid‐lowering effect.